The dragon in the jungle the Chinese Army in the Vietnam War - Li, Xiaobing 1954- (Oxford University Press, 2020)
Western historians have long speculated about Chinese military intervention in the Vietnam War. It was not until recently, however, that newly available international archival materials, including documents from China, have indicated the true extent and level of Chinese participation in the conflict in Vietnam. For the first time in the English language, this book offers an overview of the operations and combat experience of more than 430,000 Chinese troops in Indochina from 1965 to 1973. The Chinese Communist story from the "other side of the hill" is one of the missing pieces of the historiography of the Vietnam War. This groundbreaking book covers the chronological development of Chinese decision-making by examining Beijing's intentions, security concerns, and major reasons for entering Vietnam to fight against the US armed forces. It explains why China launched a nationwide movement, in Mao Zedong's words, to "assist Vietnam and resist America" from 1965 to 1972.
Keywords: China -- Zhong guo ren min jie fang jun; Geschichte 1965-1973; Vietnamkrieg; Sicherheitspolitik; China; Vietnam War, 1961-1975 / Participation, Chinese; Vietnam War, 1961-1975 / Campaigns / Indochina; China / Military policy / History / 20th century